Uncontrolled Markets and the Inflationary Process in a Centrally Planned Economy. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1989)
This paper analyzes the inflationary process in a centrally planned economy which has an uncontrolled market where prices can move more freely. The maintenance of controls over prices and rationing in the economy leads to the emergence of forces that generate inflation in the uncontrolled market, and that cause shrinkage of the controlled economy as resources move into the uncontrolled market. Decontrol of prices and production of the controlled market is the optimal policy. The adoption of this policy facilitates an increase in income and aggregate demand, which raises the equilibrium prices and total production in the economy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet